Multimodal Teaching Proposal in an English as A Foreign Language Subject - María Martínez Lirola (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2020)
XXI century society has a multimodal nature and it is referred as 2.0 era, in which the use of Information and Communication Technologies (ICTs) is essential. This implies that tertiary education needs to be adapted to this context and, therefore it is necessary to highlight multimodal teaching in University classrooms thanks to Power Point or Prezi presentations, the use of videos or social networks such as Facebook or Twitter, the use of google tools, etc. This article intends to be a contribution to highlight the importance of multimodal teaching in higher education. It describes some activities that promote multimodality used in the subject English Language V of the degree in English Studies at the University of Alicante. The selection of activities is determined not only for its multimodal nature but also because they contribute to the acquisition of competences that are essential for the labour market. In addition, a survey was prepared in order to know students’ opinions about a teaching proposal based on multimodality. The results of the survey show that students consider that multimodal teaching facilitates learning and increases their motivation. Moreover, multimodal teaching contributed to the acquisition of different social competences.